Direct Self-control of Interior Permanent Magnet Synchronous Motors with a Constant Switching Frequency - Oh, Yoon Gi; Han, Byeol; Lee, Kyo Beum (Journal of Electrical Engineering and Technology, 2022)
This paper proposes a direct self-control (DSC) for interior permanent magnet synchronous motors (IPMSMs) with a constant switching frequency. The disadvantage of the conventional DSC, which has the characteristics of low switching frequency and fast torque response in high-power systems such as railway vehicles, is that the switching frequency varies according to the operating conditions. In this study, a torque controller with a constant switching frequency is applied to overcome this problem, instead of the torque hysteresis controller for the conventional DSC. The proposed DSC uses a torque regulator with a proportional-integral (PI) controller and a triangular carrier to realize a constant switching frequency. In the transient state of the torque, the dynamic torque response is slow because both zero and active voltage vectors are selected. Therefore, only the active voltage vectors are applied during the transient state of the torque to improve the dynamic torque response. The effectiveness of the proposed DSC is verified through simulation and experimental results.
Keywords: Active voltage; Constant switching frequency; Constant-switching-frequency torque controller; Direct self control; Dynamic torques; Interior permanent magnet synchronous motor; Railway vehicles; Torque controllers; Torque response; Transient state; Constant-switching-frequency torque controller; Direct self-control; Interior permanent magnet synchronous motor; Railway vehicles